Perawatan Kompresor Udara dalam Mendukung Kinerja Mesin Penggerak Utama di Kapal MV. Tms Glory - Muhammad Usamah Naufal; Iksan Saifudin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Air compressor on board MV. Tms Glory has a vital role in supporting the performance of the main drive engine. This study evaluates the air compressor maintenance system through direct surveys, interviews with personnel, and document reviews. The results show that the implementation of preventive care has succeeded in reducing the risk of operational disruption. Challenges such as lack of resources for planned care were identified. Recommendations include the use of advanced condition monitoring technology and increased personnel training to support proactive care. This approach is expected to increase the operational availability of ships and reduce maintenance costs in the long term.